Green Synthesis of Zinc Oxide Nanoparticles from (Punica granatum L) Pomegranate Aqueous Peel Extract - Husain, Wassan Mhammed; Araak, Jawad K.; Ibrahim, Orooba M.S. (The Iraqi Journal of Veterinary Medicine, 2019)
The biosynthesis of Zinc oxide nanoparticles (ZnONPs) was done under alkaline conditions (pH 12) and temperature ≥ 80 ◦C. Mixing 10% of aqueous pomegranate peel extract (PPE) with 0.1 molar of zinc nitrate [Zn (NO3)2.6H2O], mixture was stirred at 70-80 ◦C for 15 minute and then left at room temperature overnight. The result was separated and centrifuged at 4000 rpm for 10 minutes. This process was repeated three times then the precipitate was collected and dried for using. ZnONPs were characterized by visual observation of color changes, estimate duration of synthesis compared to weight of ZnONPs was the result, UV-visible analysis, Fourier transform infrared (FT-IR), X- ray diffraction (XRD) and Scanning electron microscope (SEM). The results of this line, investigate the proper condition for ZnONPs synthesis. Result of FT-IR showed functional group related to Zn-O at (613.38 to 580.59 cm_1), whereas the result of X-RD at 2 theta diagnose the type of oxide formation as ZnO and determined particle size were found in range (20 - 30 nm). Finally, SEM image was shown crystals shape of ZnO nanoparticles. In conclusion, PPE acts as reducing agent used in synthesis of ZnO in Nano-scale size via easy and simple method.